KOTA PINTAR ALA AL-FARRABI: STUDI KRITIS FILSAFAT POLITIK AL- FARRABI - Muqsith, Awal (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2017)
Structure of an ideal state, according to al-Farraby, is similar to that of a human body by which all parts support each other in achieving perfection and collectively working in preserving life. Al-Farraby believes that the entire universe is an emanation of the first being. Quoting the words of Ahmad Musayyar,